Science, medicine, and animals (National Academies Press, 2004)
Diseases cause a staggering amount of suffering and death in both people and animals. As a result, human society has committed itself to alleviating this suffering. Toward this goal, biomedical research has included the use of animals as one component of research to understand, treat, and cure many human and animal diseases. Animals develop many of the same diseases as people, including hemophilia, diabetes, and epilepsy. Animals and humans are also susceptible to many of the same bacteria and viruses, such as anthrax, smallpox, and malaria. Because animals share so many health risks and issues with humans, they can be useful models for understanding illness and how to treat it. "Science, Medicine, and Animals discusses how animals have been and continue to be an important component of biomedical research. It addresses the history of animal research and what it looks like today, and gives an overview of some of the medical advances that would not have been possible without animal models. Finally, it looks at the regulations and oversight governing animal use, as well as efforts to use animals more humanely and efficiently.